Marketing Literature - Squires, C. author. aut Link
IX, 237 p.
Keywords: This is an important study of the publishing of contemporary writing in Britain. It analyzes the changing social, economic and cultural environment of the publishing industry in the 1990s-2000s, and investigates its impact on genre, authorship and reading. It includes case studies of Trainspotting and the His Dark Materials trilogy.